Dampak Urbanisasi Terhadap Kualitas Lingkungan di Kota Makassar - Dahlan, Mubarak (Rayhan Intermedia, 2025)
Such rapid changes due to urbanization in Makassar City have in fact affected many aspects, including social, economic, and environmental. This study aims to describe and analyze the effects of urbanization on environmental quality in Makassar City, with a focus on air and water pollution, and reduced green open space. The research method used is a quantitative approach through secondary data analysis from observations, field surveys, interviews and related agency documents. The findings of this study indicate how high levels of urbanization are related to increased air pollution from vehicle emissions, reduced water quality due to unmanaged household waste, and the conversion of green areas into residential areas and infrastructure. Likewise, uncontrolled population growth in turn exacerbates pressure on natural resources and urban sanitation systems. A recommendation offered from the results of this study is the importance of sustainable land use policies, strengthening environmental laws, and increasing public awareness..